Israel – In Search of Constitutional Common Sense - Sadowski, Paweł (Review of European and Comparative Law, 2023)
The Israeli radical judicial overhaul program, aiming to seriously weaken the judiciary, has led the country to the brink of chaos and violence, with hundreds of thousands of demonstrators in the streets, society tearing itself apart and numerous sectors of society, such as medical service or reservists of IDF, announcing a suspension of their service to a nation they fear will no longer be a democracy. Despite the strong social protest, Knesset – representing an extremely right-wing coalition – adopted on the July 24, 2023 the amendment to Basic Law: The Judiciary to bar the judiciary from striking down decisions of the government and its ministers on the grounds of such decisions being unreasonable. The measure known as the reasonableness clause (standard) is rooted in English and American case law and it is frequently used in Israel to control administrative activity. It allows the courts to strike down governmental and administrative decisions and their regulations seen as having not taken into account all the relevant considerations of a particular issue, or not given the correct weight to those considerations – even if they do not violate any particular law or administrative rulings. The current right-wing coalition, led by Benjamin Netanyahu, argues that the clause as it stands gives too much power to the judiciary, especially the Supreme Court sitting as a High Court of Justice, to interfere with the actions of the executive, and that the powers of judges, who are not elected by the public, remain out of control in this procedure. Opponents of the government’s amendment argue that this standard is crucial in helping to protect civil rights that are not fully defined in Israeli law. Eliminating the standard of reasonableness will be another step towards giving the government unlimited power. It violates not only the separation of powers principle and the rule of law but it also harms the right to good administration. Irrespective of the Supreme Court’s decision on the constitutionality of the government’s amendment, the struggle to maintain the democratic principles of the Israeli system will continue. Despite the strong social protest, Knesset – representing extremely right-wing coalition –adopted on the 24th of July 2023 the amendment to Basic Law: Judiciary to bar the judiciary from striking down decisions of the government and its ministers on the basis of being unreasonable. The measure known as the reasonableness clause (standard) is rooted in English and American case law bless and it is frequently used in Israel to control the administrative activity. It allows the courts to strike down governmental and administrative decisions and their regulations seen as having not taken into account all the relevant considerations of a particular issue, or not given the correct weight to those considerations – even if they do not violate and particular law or administrative rulings. The current right-wing coalition, led by Beniamin Netanyahu, argues that the clause as it stands gives too much scope to the judiciary, especially the Supreme Court sitting as a High Court of Justice, to interfere with the actions of the executive, and that the powers of judges, who are not elected by the public, remain out of control in this procedure. Opponents to the government’s amendment argue that this standard is crucial in helping to protect civil rights that are not fully defined in Israeli law. Eliminating the standard of reasonableness will be another step towards giving the government unlimited power. It violates not only the separation of powers principle and rule of law but it also harms the right to good administration. Irrespectively of the Supreme Court’s decision on the constitutionality of the government’s amendment, the struggle to maintain the democratic principles of the Israeli system will continue.